THE SIGNIFICANCE OF MYSTIC IDEAS IN SPIRITUAL AND SOCIAL DEVELOPMENT OF SOCIETY (American Journal of Technology and Applied Sciences, 2024)
In this article, it is analyzed that among the people of Sufism (mystics), poets, thinkers-sages emerged who left many artistic, philosophical, theological works in Arabic, Persian, Turkish and other languages.